Analisis Learning Loss dan Strategi Recovery Pasca Pembelajaran Jarak Jauh - Nurmala Rejeki (Nusantara: Jurnal Pendidikan Indonesia, 2022)
Government policies to prevent the spread of Covid-19 makes teaching and learning activities carried out online. However, after the spread of the corona virus subsided, offline learning began to be reinstated. This habit change raises several problems in the learning process. This is because students are used to online learning which has time flexibility and the limited assistance provided by educators. This study aims to analyze the problems of learning loss in students and recovery strategies for learning loss problems in students. This study uses a qualitative method. The data collection method used is through observation and interviews. The results of this study indicate that there are several learning loss problems in students, namely problems of learning enthusiasm, literacy, discipline, and politeness. Furthermore, recovery strategies that can be carried out are through socialization, parenting FGDs, literacy assistance, monitoring, and evaluation.